PERANAN BANK INDONESIA DALAM MENGATUR DAN MENGAWASI PELAKSANAAN PRINSIP KAHATIA-HATIAN DALAM PROGRAM KREDIT USAHA RAKYAT (KUR) - , Mohammad Reza ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Bank Indonesia as State institution responsible for regulation and supervision of the Banks shall also organize and supervise the implementation of KUR Program distribution made by Banks. Regulation and supervision will ensure KUR distribution implemented well channeling, based on the principle of prudence in order not to have a negative impact on the banking and financial system in Indonesia. KUR Program provides credit facility (loan) to lower middle class community without additional collateral. This research is a descriptive analysis for this study aims to provide a detailed aspects, systematic and comprehensive approaches relating to the role of the Bank Indonesia in the regulation of the application of the precautionary principle in business loan program. When they are classified according to their approach, this research is the study of literature. The results of the research it can be concluded that, firstly, KUR Program envisaged for the principle of prudence, as well as KUR delivery mechanisms that both must be carried out by the Bank. However, there are provisions that lead to violations of an element in the 5C principle (character, capacity, capital, Collateral and conditions of economy), i.e. the Collateral principle, in the special additional guarantee based on the memorandum of understanding of credit guarantees. Secondly, the role of the Bank Indonesia in the management and monitoring of the implementation of the precautionary principle in the agenda of KUR Program is a form of application of the rules have been issued by the Bank Indonesia is concerned about the effort to give credit and provide funding based on Islamic principles.